Analisis Pendapatan dan Strategi Pengembangan Usaha Tanaman Hias pada Masa Pandemi Covid-19 (Studi Kasus Toko Bunga Nararya Garden di Desa Ajung Kecamatan Kalisat Kabupaten Jember) - Oktaviana, Rina; Hawa, Tidar Aden (KUBIS, 2022)
Currently the world is shocked by the emergence of COVID-19 which has forced the government to adopt policies to minimize transmission of the virus, by reducing activities outside the home. In the midst of this pandemic, many people are starting to try something new or an interesting side, to relieve fatigue at home. One of them is a side interest in collecting various ornamental plants. A new hobby during this pandemic, many people buy various types of ornamental plants, for example in Ajung Village, Kalisat District, many people care for and buy ornamental plants. The purpose of this research is to find out what income or strategy is used by the ornamental plant business in sales at the Naraya Garden flower shop. The selection of the research location was carried out purposively, or at least deliberately considering the pre-survey being led. And based on the research results, it can be concluded that there is a significant difference between the average income before and during the pandemic. And the strategy that must be applied in this condition is to support an aggressive growth policy. The strategies that will be carried out are: Conduct socialization/training to attract the younger generation. To produce quality products, land expansion is carried out to increase the number of workers.